Magnetic and electrical transport signatures of uncompensated moments in epitaxial thin films of the noncollinear antiferromagnet Mn3Ir - James M Taylor; Edouard Lesne; Anastasios Markou; Fasil Dejene; Pranava Keerthi Sivakumar; Simon Pöllath; Kumari Gaurav Rana; Neeraj Kumar; Chen Luo; Hanjo Ryll; Florin Radu; Florian Kronast; et al. (2019)
Noncollinear antiferromagnets, with either an L12 cubic crystal lattice (e.g., Mn3Ir and Mn3Pt) or a D019 hexagonal structure (e.g., Mn3Sn and Mn3Ge), exhibit a number of phenomena of interest to topological spintronics. Among the cubic systems, for example, tetragonally distorted Mn3Pt exhibits an intrinsic anomalous Hall effect (AHE). However, Mn3Pt only enters a noncollinear magnetic phase close to the stoichiometric composition and at suitably large thicknesses. Therefore, we turn our attention to Mn3Ir, the material of choice for use in exchange bias heterostructures. In this letter, we investigate the magnetic and electrical transport properties of epitaxially grown, face-centered-cubic γ-Mn3Ir thin films with (111) crystal orientation. Relaxed films of 10 nm thickness exhibit an ordinary Hall effect, with a hole-type carrier concentration of (1.500 ± 0.002) × 1023 cm−3. On the other hand, TEM characterization demonstrates that ultrathin 3 nm films grow with significant in-plane tensile strain. This may explain a small net magnetic moment, observed at low temperatures, shown by X-ray magnetic circular dichroism spectroscopy to arise from uncompensated Mn spins. Being of the order of 0.02 μB/atom, this dominates electrical transport behavior, leading to a small AHE and negative magnetoresistance. These results are discussed in terms of crystal microstructure and chiral domain behavior, with spatially resolved XML(C)D-PEEM supporting the conclusion that small antiferromagnetic domains,